Perbandingan antara CT Score dan Saturasi Oksigen pada Pasien COVID-19 di Rumah Sakit UKI Tahun 2021 - Elizabeth, Patricia Roulin; Ruslim, Daniel (Majalah Kedokteran Andalas, 2025)
Coronavirus disease 2019 (COVID-19) is an infectious disease that has caused pandemic effects on world demographics. It is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2). COVID-19 can attack various organs, especially the lungs. The first time a COVID-19 case was discovered in Indonesia was announced on March 2, 2020. The number of casesspread rapidly in Indonesia. The objective of this study is to findout the comparison of CT scores and oxygen saturation of COVID-19 patients at UKI Hospital in East Jakarta. This study uses a cross-sectional design using medical records and data analysis using Mann– Whitney. Based on the result of the study, high CT-Score causes low Oxygen Saturation, Furthermore, there is a relationship between CT Score and oxygen saturation of COVID- 19 patients at UKI Hospital in East Jakarta with a p-value of 0.05.